If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(6x + 4) = 4x + -1 + 2x Reorder the terms: 4(4 + 6x) = 4x + -1 + 2x (4 * 4 + 6x * 4) = 4x + -1 + 2x (16 + 24x) = 4x + -1 + 2x Reorder the terms: 16 + 24x = -1 + 4x + 2x Combine like terms: 4x + 2x = 6x 16 + 24x = -1 + 6x Solving 16 + 24x = -1 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 16 + 24x + -6x = -1 + 6x + -6x Combine like terms: 24x + -6x = 18x 16 + 18x = -1 + 6x + -6x Combine like terms: 6x + -6x = 0 16 + 18x = -1 + 0 16 + 18x = -1 Add '-16' to each side of the equation. 16 + -16 + 18x = -1 + -16 Combine like terms: 16 + -16 = 0 0 + 18x = -1 + -16 18x = -1 + -16 Combine like terms: -1 + -16 = -17 18x = -17 Divide each side by '18'. x = -0.9444444444 Simplifying x = -0.9444444444
| 7m+1m=3 | | (5x+4)+(9x+5)= | | 4x+126+22=180 | | 2q+16-17q=-14-18q | | 8.50x+5=90 | | 4a(2a+6)= | | 3b+6=4b | | -26=-3k-8 | | -16+3t=2t | | 3n-2n=30 | | 6(y-5)-4=6(-4y+5)-6y | | 3(x+2)x=18 | | (-7+1)+(-x+2)= | | 0=10cos(3x) | | 5x^7/6=10 | | (4f-6)/4=1 | | -1=-8w+23 | | 9x+57+51=180 | | 9-4=-4w+6w | | 4g-7g+7=-g-5 | | (x+3)(x-8)=x^2-4x+24 | | 3p/8-15-33 | | 18x+14y+63z=5 | | -6can+2x-11=-2(2X-3)+4 | | 2s+8s=20 | | 0.04x+0.06(10000-x)=720 | | F(x)=50(6) | | a^2-4a+3a-12=0 | | -7u(u-7)=-4 | | -3n-8=9n+6 | | -2h=10 | | 3(k-4)-2(k+2)-14=-22 |